THE INFLUENCE OF LEADERSHIP STYLE AND WORKLOAD ON THE PERFORMANCE OF EMPLOYEES OF PT. PELABUHAN INDONESIA (PERSERO) REGIONAL 4 MAKASSAR - Amaliah Hatta; Muhammad Yusuf; Nurinaya, Nurinaya (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this research is to determine The Influence of Leadership Style and Workload on PT Employee Performance. Indonesian Harbor (Persero) Regional 4 Makassar. This type of research is quantitative descriptive. This sample was taken from the PT. Indonesian Harbor (Persero) Regional 4 Makassar. The type of data used in this study is quantitative data obtained from distributed questionnaires and is related to the problem under study. Data collection was carried out by observing and distributing questionnaires. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert scale method. Based on the results of data research using statistical calculation through the Statistical Package for the Social Science (SPSS) application version 26 regading The Influence of Leadership Style and Workload on PT Employee Performance. Indonesian Harbor (Persero) Regional 4 Makassar which has been discussed in the previous chapter, then the author draws an important conclusion, namely leadership style and workload have a positive and significant effect on employee performance. The leadership style needs to be further improved, especially the ability to motivate and control emotions because from the results of the second respondent's response, this is still a shortage of leaders and employee workload needs to be paid more attention, especially to working conditions because it can be seen from the research results that working conditions are still something that people complain about. employee.